Against 'Against Slagle's Reading'. (10th August 2022) - Slagle, Jim
Abstract: Serdal Tümkaya has argued that my critique of eliminative materialism makes several missteps. He argues that eliminativism should be taken as a methodology not a settled conclusion, and the final product may well retain some folk psychology concepts. I respond that methodological eliminativism does avoid self‐defeat but does not pose a problem for the folk psychologist. Plus, insofar as eliminativism is not eliminating the propositional attitudes but accomodating or translating them, it is not distinct from other, less extreme forms of materialism.